A comparison between Polish Holstein-Friesian and F1 hybrid Polish Holstein Friesian × Swedish Red cows in terms of milk yield traits - Solarczyk, Paweł (Array, 2021)
The intensive breeding work of Holstein-Friesian cattle has led to the decrease in the diversity within the population and to inbreeding depression, which may impair its functional traits. In addition, as shown by the research, production traits are negatively correlated with functional traits such as reproduction, health, and longevity, which have a very strong impact on the profit of dairy farms. The aim of this study was to compare milk yield traits of hybrids obtained by crossbreeding of Polish Holstein Friesian (PHF) cows and Swedish Red (SRB) bulls with values obtained for pure PHF cows. For the study, 100 primiparous cows were selected and divided into two groups. The experimental group consisted of 50 crossbreds (PHF×SRB), while the control group consisted of 50 purebred PHF cows. The study showed a higher content of milk components (fat by 11.78 %, protein by 9.06 %, dry matter by 5.75 %) in PHF×SRB, as compared to PHF. A lower level of SCC (by 38.94 %) has also been shown in hybrids, which indicates their higher resistance to udder diseases. The experiment demonstrated a highly significant impact of heterosis on performance parameters and technological quality of milk in F1 generation obtained as a result of crossbreeding between PHF cows and SRB bulls.